Analysis of the Course of Symptoms in Patients with Osteoarthritis Secondary to Acetabular Dysplasia Treated with Physical Therapy - SHIRATSUCHI, Hideaki; YAMADA, Takumi; SENOH, Yoshikazu; HIRAO, Ricoh (Physical Therapy Japan, 2022)
Objectives: The purpose of this study was to clarify whether there is a difference in temporal changes in patients with secondary osteoarthritis of the hip according to the stage of the disease when physical therapy was applied.Methods: Fifty subjects were classified into three groups using the Kellgren/Lawrence classification: 14 subjects in the Grade 1 (KL1) group, 20 subjects in the Grade 2 (KL2) group, and 16 subjects in the Grade 3 (KL3) group. Physiotherapy intervention was provided for 3 months. Pain, activities of daily living (ADL), and physical functions were periodically measured.Results: The KL3 group had more pain and lower ADL and physical functions throughout the 3 months, but showed improvement over the 3 months regardless of KL classification. Age-adjusted flexion, abduction, and internal rotation range of motion (IR ROM) were lower in the KL3 group, with no significant change in IR ROM over the 3 months.Conclusion: Physical therapy for secondary OA of the hip showed improvement in pain, ADL, and physical functions over the 3 months regardless the stage of the disease.